Semiotic Analysis of Animated Advertising Pocari Sweat - Astri Dwi Andriani; Muhamad Yusuf Habibie (International Journal of Economics, Business Management and Accounting (IJEBMA), 2022)
Animated advertising is a promotional media that uses animation to introduce its products. One product that uses animation as an advertising medium is Pocari Sweat. In October 2020, Pocari Sweat issued an advertisement using its anime animation techniques with the theme Pocari Sweat: Sweat For Dream. To be able to find out the meaning of verbal and non-verbal semiotic messages contained in the Pocar Sweat: Sweat for Dream advertisement. This research is qualitative research using Saussure's semiotic model approach to analyze objects through the stages of signs, markers and signs, while Herbert Blumer's symbolic interaction theory analyzes objects through verbal and non-verbal signs. The results of this research show that the message to be conveyed in this advertisement is an invitation to stay enthusiastic and not give up easily in achieving your dreams, which is packaged through verbal and non-verbal signs in this advertisement